The Role of Educational Support, Social Support, Income Expectations and Personality on Student's Entrepreneurial Interests in Riau, Indonesia - Astri Ayu Purwati; Muhammad Luthfi Hamzah; Zulfadli Hamzah; Ermina Rusilawati (International Journal of Economics Development Research (IJEDR), 2022)
Every year there are university graduates who should be able to improve the quality of human resources in Indonesia. The reality is that college graduates are more directed to the formal sector so when jobs in the legal industry do not grow, people do not try to create their careers. This research aims to analyse the effect of Higher Education Learning Support, Social Support, Income Expectations and Personality on Student Entrepreneurial Interests in Riau, Indonesia. The sample in this research is 400 students in Pekanbaru, Riau. The population in this study were final semester students (6,7,8) at a university in Pekanbaru, Riau. And by using research samples taken from as many as 400 people according to the sample criteria with solving calculations. The data analysis technique used tested the validity and reliability as well as the hypothesis as evidenced by multiple linear regression analysis. Based on the study's results, it can be concluded that the variables in this study consisting of college support, social support, income expectations and personality significantly influence student interest in Riau. Keywords: Educational Support, Social Support, Income Expectations, Personality, Entrepreneurial Interest